(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The aim of this work was to irradiate brazilian grape tree wines with gamma radiation (Co60) to investigate the effect of radiation on its components and to create a new product for the superior quality fermented beverages market. For this wine was produced in an artisan way, but with all the care of hygiene and sanitation. The brazilian grape tree was femented for five days and the wine was then filtered and stored in inert material containers then irradiated at 2.5 and 5 kGy doses. The samples were evaluated in relation to the radiation doses used. Physical and chemical analyzes of pH; total and volatile acidity; alcohol content; anthocyanins; tannins and colorimetry were performed. As a result, in most product analysis, had little effect on irradiation, except for anthocyanins and tannins. For this can be concluded that it is possible to develop a new fermented drink based on brazilian grape tree, according to the standards required by the legislation and that the irradiation at the dose of 5kGy was the sample that shown to have the most effect on the color because it was the one that degraded most molecules of anthocyanins and tannins.